Female streetworking prostitution and HIV infection in Glasgow. Issue 6857 (3rd October 1992) - McKeganey, N.; Barnard, M.; Leyland, A.; Coote, I.; Follet, E.
Abstract : OBJECTIVES--To identify the extent of HIV infection and injecting drug use among female streetworking prostitutes in Glasgow; to estimate the size of the female streetworking prostitute population in the city; and to estimate the number of HIV positive women working as prostitutes on the streets in Glasgow. DESIGN--Observation and interviewing of female prostitutes over seven months in red light district; analysis of saliva samples for presence of antibodies to HIV; capture-recapture approach to estimating the size of the female streetworking prostitute population. SETTING--Glasgow. SUBJECTS--206 female streetworking prostitutes. MAIN OUTCOME MEASURES--Number of women with antibodies to HIV, self reported use of injecting drugs, history of contact with 206 women. RESULTS--Saliva samples were requested from 197 women; 159 (81%) provided samples. Four (2.5%, 95% confidence interval 0.7%-6.3%) of the samples were positive for HIV, all of which had been provided by women who injected drugs. Of the 206 streetworking women contacted 147 (71%) were injecting drug users. About 1150 women are estimated to work on the streets in Glasgow over a 12 month period. CONCLUSIONS--HIV is not as widespread among female prostitutes as many reports in the tabloid press suggest. A greater proportion of female streetworking prostitutes in Glasgow are injecting drugs than has been reported for other British cities.